Immunization status of children attending immunization clinic at a tertiary care government hospital of Agra district - Mehto, Amit Kumar; Negi, Rudresh; Sembiah, Sembagamuthu (International Journal Of Community Medicine And Public Health, 2020)
Background: Immunization coverage in India has increased over the decades and has led to decrease in child mortality. However challenges remain in terms of partial and no immunization and its causes. This study assesses the immunization status of children attending the immunization clinic and the reasons for partial or non-immunization at tertiary care government hospital of Agra district. Methods: It was a cross-sectional study and included all children between ages 9 months and 5 years during the study period. A pre-design, semi-structured, face validated and pilot tested was used after written informed consent of care givers. Data was analysed using SPSS. Results: Of the 652 children enrolled the mean age was 24.2 months. Most of the children were born in an institution (95.2%) and were from an urban area (81.9%). More than one-thirds of the children, 40.2% (n=262) were fully immunized for their age. Of the 390 partially or unimmunized the most common cause was no knowledge of vaccination‎/next dose (n=120, 30.8%) and inaccessibility/transport issues (n=120, 30.8%). On logistic regression sex of the child, mother’s education and occupation, family type were found to be significantly associated with the immunization status. Conclusions: This study indicated low full immunization and high partial immunization among attendees of immunization clinic in the institution; with lack of knowledge and transport difficulties being the primary reasons for it.